Fotoinativação de biofilmes de Pseudomonas aeruginosa utilizando porfirinas tetra-catiônicas - Urquhart, Carolina Gonzalez (2022)
Pseudomonas aeruginosa is an opportunistic pathogen that can be found in diverse environments and is often associated with serious infections in immunocompromised patients. This microorganism has a notorious ability to form biofilms, thus being able to colonize medical devices, wounds and burns. Biofilms are characterized as bacterial communities surrounded by an extracellular matrix. This phenomenon makes microorganisms more resistant, resulting in a decrease in the effectiveness of treatment with antimicrobial agents. As a result, new treatments are being developed to reduce this problem, such as photodynamic therapy. This process is based on the use of a photosensitizer and the subsequent application of visible light to generate reactive oxygen species, thus causing cell death. In this context, the present work aims to evaluate the antimicrobial and antibiofilm activities of tetra-cationic porphyrins against Pseudomonas aeruginosa (PA01) and clinical isolates. The determination of the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of porphyrins 3-H2TMePor and 4-H2TMePor front PA01 were performed by assays of antibacterial activity in different concentrations, being submitted to dark conditions and irradiation with white light for 120 minutes. The photosensitizer (PS) 4-H2TMePor was chosen for the other tests, as it showed better MIC and MBC activity. The main photoinactivation mechanism in the use of PS was mediated by singlet oxygen. In the cell viability curve assay, 4-H2TMePor porphyrin under white light irradiation at a concentration of 2xMIC inhibited bacterial growth in 60 minutes and MIC in 90 minutes. Porphyrin 4- H2TMePor associated with the antimicrobial Imipenem (IMP) against PA01 showed synergistic activity. Biofilms were formed with standard strain PA01 and three clinical isolates. To evaluate the antimicrobial activity of PS on the biofilm formed, the biofilm destruction assay was performed, using concentrations of MIC, 2xMIC and 4xMIC for each microorganism. The PS associated with the IMP potentiated the destruction of the biofilm against PA01 when compared to the positive control. The cytotoxicity assay with porphyrin 4- H2TMePor proved to be non-toxic against healthy human keratinocyte cells and mouse fibroblasts. Atomic force microscopy showed a common morphology for PA01. The nanomechanical properties were tested comparing PA01 without and with ½MIC treatment. The treated control showed lower adhesion strength, greater cell wall deformation and greater dissipation energy compared to untreated PA01, indicating interference of porphyrin directly with the cell wall of the microorganism even at concentration below the MIC. In view of these results, water-soluble tetra-cationic porphyrin showed excellent antimicrobial and antibiofilm activity, in addition to presenting good safety of use, showing to be a potential photosensitizer against infections caused by P. aeruginosa.